2020
DOI: 10.5194/acp-20-6541-2020
|View full text |Cite
|
Sign up to set email alerts
|

On the forcings of the unusual Quasi-Biennial Oscillation structure in February 2016

Abstract: Abstract. The westerly phase of the stratospheric Quasi-Biennial Oscillation (QBO) was reversed during Northern Hemisphere winter 2015/2016 for the first time since records began in 1953. Recent studies proposed that Rossby waves propagating from the extratropics played an important role during the reversal event in 2015/2016. Building upon these studies, we separated the extratropical Rossby waves into different wavenumbers and timescales by analyzing the combined ERA-40 and ERA-Interim reanalysis zonal wind,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…3c of Lin et al (2019). This result is also consistent with the findings of Li et al (2020), who showed the contribution of strong Kelvin wave activity related to an El Niño event to the long-lasting westerly jet near 20 hPa. MRG waves ( Fig.…”
Section: General Characteristics Of Zonal Wind and Equatorial Wavessupporting
confidence: 91%
See 3 more Smart Citations
“…3c of Lin et al (2019). This result is also consistent with the findings of Li et al (2020), who showed the contribution of strong Kelvin wave activity related to an El Niño event to the long-lasting westerly jet near 20 hPa. MRG waves ( Fig.…”
Section: General Characteristics Of Zonal Wind and Equatorial Wavessupporting
confidence: 91%
“…2) during the disruption. The enhanced Kelvin wave activity during the disruption period was caused by the enhanced convective activity associated with strong El Niño events (Li et al, 2020). Overall, we found that convectively coupled equatorial waves are enhanced during the QBO disruption, which seem to be associated with El Niño.…”
Section: Contributions Of Rossby Waves and Mrg Wavesmentioning
confidence: 57%
See 2 more Smart Citations
“…In addition, sudden stratospheric warmings (SSWs) and quasi-biennial oscillation (QBO) events can dynamically couple the entire atmosphere from the lower atmosphere to the ionosphere (Li et al, 2020;Yamazaki et al, 2020;Yadav et al, 2019;Matthias and Ern, 2018;Stray et al, 2015).…”
Section: Introductionmentioning
confidence: 99%